2013
DOI: 10.1007/s12263-013-0340-z
|View full text |Cite
|
Sign up to set email alerts
|

Obesity polymorphisms identified in genome-wide association studies interact with n-3 polyunsaturated fatty acid intake and modify the genetic association with adiposity phenotypes in Yup’ik people

Abstract: n-3 Polyunsaturated fatty acids (n-3 PUFAs) have anti-obesity effects that may modulate risk of obesity, in part, through interactions with genetic factors. Genomewide association studies (GWAS) have identified genetic variants associated with body mass index (BMI); however, the extent to which these variants influence adiposity through interactions with n-3 PUFAs remains unknown. We evaluated 10 highly replicated obesity GWAS single nucleotide polymorphisms (SNPs) for individual and cumulative associations wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
1
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 61 publications
2
22
1
1
Order By: Relevance
“…Our study also suggests that PUFA intake could modify the genetic association with body composition. This is in accordance with findings from a previous study which detected a significant interaction between a 12 obesity SNPs' GRS and omega-3 PUFA and BMI (Lemas et al 2013). In addition to the interaction with GRS, several nominal interactions with FTO and dietary fat were found; thus, FTO interacted with total fat and MUFA intake to modify its effect on BFM.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our study also suggests that PUFA intake could modify the genetic association with body composition. This is in accordance with findings from a previous study which detected a significant interaction between a 12 obesity SNPs' GRS and omega-3 PUFA and BMI (Lemas et al 2013). In addition to the interaction with GRS, several nominal interactions with FTO and dietary fat were found; thus, FTO interacted with total fat and MUFA intake to modify its effect on BFM.…”
Section: Discussionsupporting
confidence: 92%
“…In this regard, it should be noted that from a clinical point of view, the categorization of a genetic score into a dichotomous variable could be more useful for clinical decision making (Horne et al 2005). The analyses demonstrated that the GRS as a continuous variable predicts \1 % of the BMI variation (0.16 %) in concordance with most of previous studies (Li et al 2010a;Takeuchi et al 2011;Peterson et al 2011;Lemas et al 2013). Nevertheless, our GRS explained 1.59 %.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…We have shown that RBCs and hair nitrogen isotope ratios ( 15 N/ 14 N, expressed as d 15 N, as defined in Participants and Methods) are strongly correlated (>0.8) with the RBC long-chain n-3 PUFAs EPA and DHA because all 3 measures are elevated in fish and marine mammals, a large component of the traditional YupÕik diet (5)(6)(7). Intakes of EPA and DHA are high and quite variable in YupÕik people (6); therefore, associations with health are of particular interest for further study (8)(9)(10)(11). Because d 15 N is relatively simple and inexpensive to assay, several recent studies have used d 15 N as a surrogate measure of n-3 PUFA intake (10,12,13).…”
Section: Introductionmentioning
confidence: 96%
“…Intakes of EPA and DHA are high and quite variable in YupÕik people (6); therefore, associations with health are of particular interest for further study (8)(9)(10)(11). Because d 15 N is relatively simple and inexpensive to assay, several recent studies have used d 15 N as a surrogate measure of n-3 PUFA intake (10,12,13). However, EPA and DHA derive from marine fats, whereas elevated d 15 N derives from marine protein, and these components are sometimes rendered and eaten separately (e.g., as seal oil and seal meat).…”
Section: Introductionmentioning
confidence: 99%